Study on intervention effect of Wearable Cyborg HAL through narrative analysis - Ikemoto, Shiori; Sankai, Yoshiyuki; Sakurai, Takeru (Frontiers in Psychology, 2025)
BackgroundThe medical effectiveness of Cybernics Treatment with the Wearable Cyborg HAL (Hybrid Assistive Limb) has been verified, and its treatment method has started to be used in many countries around the world. However, the focus of medical evaluations has predominantly been on simple measurement evaluation of physical function, while Patient Reported Outcome (PRO), which encompass various evaluation axes of patients, remain largely unexplored. The mental/psychological field has the potential to develop cutting-edge fields targeting individuals. As the social implementation of HAL progresses, it is important to capture how the physical intervention by HAL affects not only the physical function but also the mental state and social activities of individual users. This approach will help us understand the various aspects of the effects of Cybernics Treatment using HAL.ObjectiveIn order to elicit deeper narratives of HAL users, this study aims to capture how HAL users with limited physical functionality have changed physically, mentally and socially due to using HAL, through a narrative analysis utilizing counseling methods. Based on the results, the significance of using HAL will also be discussed.MethodsWe analyzed the narratives of nine HAL users who received the services of “Neuro HALFIT.” During the interview survey, we also visualized the narratives using mathematical engineering methods (cluster analysis, dendrogram) based on the similarity distance matrix between the association items and elicited them by deepening the narratives through counseling methods and captured the state of change in the physical, mental, and social aspects of the subjects.ResultsThe results suggested that “Neuro HALFIT” improved physical function and provided mental and social improvements. These three aspects influenced and circulated each other, advancing toward improvement and enhancement, and the “Mutual feedback structure model in physical, mental, and social aspects of patients” was proposed and presented. Based on the above analysis, it was considered that the greatest significance of using HAL was to help many people with fixed disabilities or those who were considered to have no treatment to turn the process of this model without losing hope and to participate in society with a sense of fulfillment in their lives.